Indicadores de desempenho e sua importância para um eficaz planejamento de lavra de curto prazo e operacional - Vilson Carlesso dos Reis (2019)
Mining in Brazil is one of the pillars supporting the country’s GDP (gross domestic product). Its execution requires technique and expertise, as there are several stakeholders involved. In a mining venture, the value chain conducts this business to achieve its objectives. The mine planning has a great influence on its performance, because it is through it that the organization is based to offer its products to the market and, consequently, a low compliance with the established premises will bring undesirable inconveniences. Within the planning, the short-term one is dedicated to operationalizing the plans made possible by the long- and medium-term teams, in addition to meeting market variations. The indicators that control this process are of great importance, because a misidentification inserted in the various criteria that compose it can guide managers to inefficient decision making, weakening the business. The objective of this work will be to study the variables inserted in the production process of the short-term mining plan that support the assertiveness of the adherence and compliance indicators. The lean manufactoring method was used for this purpose, employing its management, control and deviation analysis tools, identifying the main causes of failure to reach 100% adherence to the mine effectiveness indicator. In this work, it was noted that with the applied methodology leveraged the mining effectiveness indicator, determining the main causes for not achieving 100% adherence of this indicator.